Comparison Between Proprioceptive Neuromuscular Facilitation and Neuromuscular Re-Education in Patients with Bell’S Palsy: Proprioceptive Neuromuscular Facilitation and Neuromuscular Re-Education in Patients with Bell’S Palsy - Avaid, Ana; Majeed , Sidra; Naseem, Nimra; Sheraz, Zainab; Tariq , Komal; Nida Bukhari , Syeda (Pakistan Journal of Health Sciences, 2022)
The condition known as Bell’s palsy results in the weakness of fascial muscles causing it to sag and stiffen on that side. It results from damage to the 7 cranial nerve. objective: To identify the comparative effects between the PNF and neuromuscular re-education. Methods: It was randomized clinical trial with non-probability purposive sampling. Data were collected from Aziz Fatima, DHQ, Allied and MTH hospital of Faisalabad. The study consisted of 30 patients (males and females), 15 participants were randomly divided in each group by lottery method. Group A treated by proprioceptive neuromuscular facilitation with conventional physical therapy that include EMS and home plan exercises. Group B treated by neuromuscular re-education facilitation techniques with conventional physical therapy treatment. Total treatment was of 4 days per week for 4 weeks. Data were analyzed by SPSS version 21.0. Results: The findings indicated that Group A had a considerably greater value on the Facial Disability Index (FDI). Group A differed significantly from Group B in each single element (physical and social functioning), while Group B showed very moderate recovery on FDI. Conclusions: After completing four weeks of treatment, PNF demonstrated considerable reduction in facial dysfunction in conjunction with conventional PT treatment. In the case of facial paralysis, proprioceptive neuromuscular facilitation combined with conventional treatment is more efficient than neuromuscular re-education combined with conventional PT.